Frequency of Preterm Birth in Pregnant Female Residents and Impact of Working Hours on Preterm Birth - Sumaira Nadeem, Madiha Fatima, Samia Rafique, Ayesha Abdul Sattar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Varying work schedules are suspected of increasing risks to pregnant women and fetal wellbeing. Aim: To compare mean working hours in females residents with preterm birth and full term birth. Methodology: It was a descriptive cross sectional study. Female residents (n=163) were enrolled through non-probability consecutive sampling. All pregnant female residents meeting inclusion criteria were enrolled after informed consent. Their basic information like age, parity; gestational age at delivery was recorded. Their working hours per week were noted. They all were followed till their delivery. Data was evaluated by using SPSS v.24. Chi square was applied with P-value of <0.05 was considered as significant. Quantitative variables were presented as mean±SD while categorical data was presented as percentage. Results: Mean age of female doctors was 29.22±1.81 years. A total of 28(17.18%) females had preterm birth while 135(82.82%) had term deliveries. The mean working hours were statistically higher in doctors having preterm birth i.e. 67.11±1.97 hours / week with p-value < 0.05. Practical Implication: As there is a high incidence of preterm births among our pregnant females residents and there is lack of local data that specifically addresses this health issue thus current study was planned. This study highlighted relationship of duty hours and adverse birth events during pregnancy like preterm bith, pre-maturity thus established the significance of duty stress because of long duty hours as a poor prognostic indicator for pregnancy outcome. Conclusion: It was concluded that frequency of preterm birth in female residents having long duty hours was considerably high i.e. 17.18%. Hence pregnant doctors must be given relaxation in their duty hours especially in their 3rd trimester to minimize the risk of poor fetal and maternal outcome. Keywords: Preterm Births, Duty Hours, Pregnant Residents and Parity.